CdS:PMMA nanocomposite solid films with enhanced properties. (September 2015) - Padmaja, S.; Jayakumar, S.; Balaji, R.
Abstract : Size tunability and enhanced optical properties of cadmium sulphide (CdS) nanoparticles entrapped in polymethyl methacrylate (PMMA) matrix were presented in this paper. The three-dimensional quantum confinement of CdS in the PMMA matrix was achieved by the in situ technique. X-ray diffraction results show the presence of CdS in the PMMA matrix for higher concentration of CdS nanoparticles (1:20). The particle size and energy band gap were determined by UV–visible spectroscopy. The photoluminescence spectrum shows broadened surface trapped emissions that are shifted towards the blue region. The formation of CdS and its stoichiometric ratio has been confirmed using X-ray photoelectron spectroscopy. The transmission electron microscope results reveal the uniform distribution of nanometre sized particles in the PMMA matrix. The size distribution of CdS nanoparticles in the nanocomposite was carried out by atomic force microscope.